Domestic Syndications : Background Note - World Bank Group (World Bank, Washington, DC, 2016)
This background note is intended to assist debt management offices (DMOs) in assessing whether a bond placement scheme combining auctions and syndications is an appropriate strategy in their markets and, if so, to assist them in designing the corresponding procedures.